Mechanisms of multi-species mealybug invasions in Hainan Island of China: Integrating niche, distribution, and habitat drivers - Qin Si; Jie Hu; Zhong Hua; Jian Wang; Mulan Ji; Gaochao Xu; Binxin Wu; Yanjing Zhang (PLoS ONE, 2025)
Mealybugs, highly invasive pests causing global agricultural damage, threaten China’s tropical Hainan Island—a critical biosecurity zone. This study investigates spatial patterns, interspecific interactions, and environmental drivers of 15 invasive mealybug species using integrated ecological niche modeling (Maxent), niche/range overlap analyses, Joint Species Distribution Models (JSDM), and Structural Equation Models (SEM). Our research revealed that a strong coastal-inland richness gradient emerged, where humid tropical climates and monoculture plantations supported 11–15 species in eastern coasts, whereas topographic complexity limited invasions to 0–5 species in forested mountains. In parallel, high niche overlap (I ≥ 0.67) among species reflected climate-mediated thermal tolerance and habitat-driven broad host preferences. Range overlap patterns diverged: high-overlap pairs (e.g., Planococcus minor and Paracoccus marginatus , I > 0.8) coexisted via adaptation to 24–28°C and generalist hosts, whereas low-overlap pairs (e.g., Icerya purchasi and Phenacoccus nigra , I = 0.37) segregated through host specificity. Mechanistically, JSDM confirmed these patterns, revealing competitive exclusion where resource overlap and thermal adaptation divergence occurred (e.g., P. marginatus vs. Dysmicoccus brevipes ), versus coexistence promoted by host specialization (e.g., Ceroplastes psidii ’s rubber tree specificity versus P. marginatus ’s generalism), reproductive strategy divergence (parthenogenesis vs. seasonal outbreaks), and external environmental factors. Ultimately, SEM analyses and Linear regression identified significant positive correlations between habitat conditions and species suitability (R² = 0.71, p < 0.001), with habitat type as the dominant driver (total effect = 0.48), where climate and topography indirectly regulated suitability through habitat characteristics (e.g., elevation, latitude) while pest-infested areas directly enhanced suitability (path coefficient = 0.24). Our research framework elucidates multi-species invasion assembly mechanisms, new insights and theoretical support for the management of 15 invasive mealybug species, providing a solid foundation for optimizing future species distribution models, and validating the methodological value of integrated modeling (JSDM-SEM) in disentangling invasion complexities.